Dissipatively coupled waveguide networks for coherent diffusive photonics - Sebabrata Mukherjee; Dmitri Mogilevtsev; Gregory Ya. Slepyan; Thomas H. Doherty; Robert R. Thomson; Natalia Korolkova (Nature Communications, 2017)
Diffusive light propagation represents a valuable additional tool for integrated photonic technologies. As an example, here the authors experimentally demonstrate optical equalisation of coherent light propagating in a femtosecond laser written circuit which simulates a dissipatively-coupled quantum chain.